Improving the State Regulatory System of the Agribusiness - Latysheva, Zoya Ivanovna; Skripkina, Elena Viktorovna; Kopteva, Natalia Alekseevna; Zhilyakov, Dmitri Ivanovich; Nikiforov, Andrey Igorevich (Cuestiones Políticas, 2020)
The article aims to improve the state agribusiness regulatory system. It is established that the state regulatory system for agribusiness must be based on the application of a reasonable protectionism policy, guaranteeing food security through a system of tariffs and customs taxes on imported food products. The authors demonstrate the need to create a favorable climate for foreign investors, establish joint ventures in the agricultural business, provide state guarantees to foreign creditors by importing advanced equipment and technology, as well as finance key areas of science on business problems. agricultural. The theoretical and methodological basis of this study is an abstract logical method, induction, deduction, analysis, synthesis and systematization methods; as well as the statistical, economic and graphic methods used to study the levels and trends of change in the parameters of agricultural development in the current stage. In conclusion, it is revealed that parities in agricultural prices must include parity with consumer prices. for rural residents. The wages of employees in rural areas must guarantee the reproduction of the labor force and the development of the social sphere.